The Number of Glycine Residues Which Limits Intact Absorption of Glycine Oligopeptides in Human Jejunum - Adibi, Siamak A. (1977)
Studies were performed to determine whether glycine peptides of four or more glycine residues can be transported by the peptide carrier system, previously shown to transport diglycine and triglycine. When human jejunum was perfused with tetraglycine solutions, the rate of tetraglycine disappearance increased linearly as the concentration was increased over the range of 12.5-50 mM, however, the rate was slow in comparison to diglycine and triglycine disappearance rates. Glycylleucine, a competitive inhibitor of diglycine and triglycine transport, was without effect on the disappearance rate of tetraglycine, but increased (over sixfold) appearance rates of triglycine and diglycine (products of tetraglycine hydrolysis). These products were the results of hydrolysis of tetraglycine by the brush border enzymes because cytosol fraction lacked any hydrolase activity against tetraglycine. When a jejunal ring preparation was incubated with tetraglycine, there was intracellular accumulation of diglycine and triglycine but not of tetraglycine. The rates of glycine uptake were always markedly greater from diglycine and triglycine solutions than from corresponding glycine or tetraglycine solutions; rates of glycine uptake from tetraglycine solutions were either similar to or greater than rates from glycine solutions, depending on the infusion concentration. When the number of glycine residues was increased to hexaglycine, the phenomenon of a greater rate of glycine uptake from a peptide versus a free amino acid solution was no longer apparent. In vitro assay of peptide hydrolase activity of the luminal fluid revealed no activity against diglycine and triglycine and only trace activities against tetraglycine, pentaglycine, and hexaglycine. The above observations suggest the following conclusions: (a) the disappearance of tetraglycine in the human jejunum is accomplished principally by hydrolysis by brush border oligopeptidases; (b) the rate limiting step in the uptake of glycine from tetraglycine or higher peptides is due to hydrolysis of these peptides to absorbable products.